Impact Analysis of Islamic Economics on Economic Growth: A Cross-Country Evidence - Alaka, Abdullahi (Li Falah: Journal of Islamic Economics and Business, 2024)
This study aims to assess the impact of Islamic economics, specifically through Islamic financial instruments like sukuk, murabaha, and musharaka, on economic growth in selected Muslim-majority countries (Indonesia, Libya, Malaysia, Nigeria, Qatar, and Saudi Arabia) over the period 2013-2021. The research addresses a gap in the literature, as previous studies have mainly focused on theoretical frameworks or the adoption of Islamic finance without fully examining its relationship with economic growth. Using a quantitative approach, the study employs a co-integration test and the Panel Random Effects Model to analyze the data. The findings show that Islamic financial instruments significantly contribute to economic growth, with a 1% increase in these instruments leading to a 0.0039% rise in GDP. Additionally, governance effectiveness and population growth positively affect economic growth. The study concludes that Islamic economics can serve as a viable alternative to conventional systems, promoting sustainable development. The research suggests that policymakers should focus on increasing public awareness of Islamic finance and removing regulatory barriers to harness its full potential for economic growth.